CROSSFIT AS A FACTOR OF PROFESSIONAL ORIENTATION OF CADETS OF THE MINISTRY OF INTERNAL AFFAIRS OF THE ACADEMY OF THE REPUBLIC OF UZBEKISTAN - Mirzakulov Akrom Gafurzhanovich (PEDAGOGS, 2024)
Abstract: The article discusses the main directions of physical training of students of cadets of the Ministry of Internal Affairs of the Academy of the Republic of Uzbekistan.